2013
DOI: 10.3109/01612840.2013.854543
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Psychiatric and Medical High Fidelity Patient Simulation Scenarios: Effect on Nursing Student Knowledge, Retention of Knowledge, and Perception

Abstract: High fidelity patient simulation (HFPS) has become an increasingly popular teaching methodology in nursing education. To date, there have not been any published studies investigating HFPS scenarios incorporating medical and psychiatric nursing content. This study utilized a quasi-experimental design to assess if HFPS improved student knowledge and retention of knowledge utilizing three parallel 30-item Elsevier HESI(TM) Custom Exams. A convenience sample of 37 senior level nursing students participated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Participants reported increased confidence in their ability to administer and teach someone how to administer ORT, prepare ORT solution, recognise the signs and symptoms of moderate to severe dehydration and effectively treat patients with ORT technique. Several studies have found similar results to our study, in the context of evaluating students’ perspectives in their training, including a study conducted by Kameg et al in 2013, which similarly evaluated the effects of simulation-based training on student retention of knowledge in a clinical setting and performance in hands-on evaluation [3]. While these previous studies did show large improvements in confidence after completing simulation exercises, none was conducted in the context of a medical trip.…”
Section: Discussionsupporting
confidence: 86%
“…Participants reported increased confidence in their ability to administer and teach someone how to administer ORT, prepare ORT solution, recognise the signs and symptoms of moderate to severe dehydration and effectively treat patients with ORT technique. Several studies have found similar results to our study, in the context of evaluating students’ perspectives in their training, including a study conducted by Kameg et al in 2013, which similarly evaluated the effects of simulation-based training on student retention of knowledge in a clinical setting and performance in hands-on evaluation [3]. While these previous studies did show large improvements in confidence after completing simulation exercises, none was conducted in the context of a medical trip.…”
Section: Discussionsupporting
confidence: 86%
“…They identified a desire for more exposure to simulation and debriefing. Kameg et al (2013) found no improvements in student knowledge. However, further investigation indicated that HFHS improved student knowledge for those students needing remediation and learning support.…”
Section: High-fidelity Simulationmentioning
confidence: 85%
“…The skills and knowledge needed to recognize and provide effective nursing care for mentally ill patients experiencing chronic medical conditions or physical decline are a challenge for nursing students (Unsworth, McKeever, & Kelleher, 2012;Kameg, Englert, Howard, & Perozzi, 2013). HFHS has been utilized to promote student knowledge and skill development in cases of complex nursing care management that occur in mental health nursing practice.…”
Section: High-fidelity Simulationmentioning
confidence: 99%
“…Some of the studies reported their methods of ensuring the validity and reliability of results (Kameg et al, 2010;Szpak & Kameg, 2013), but in a number (Beckford, 2013;Oliver, Ambrose, & Wynn, 2011; Spinner-Gelfars, 2013) this was not addressed. Four studies used some form of validated assessment tool to provide objectivity and increased reliability of outcome measures Kameg et al, 2010;Kameg, Englert, Howard, & Perozzi, 2013;Szpak & Kameg, 2013).…”
Section: Qualitymentioning
confidence: 99%